LOS CAMIONES CHECOS - Solano Cornejo, David (1997)
Paico Peru is a subsidiary of an Asian automotive company and is dedicated to the import and sale of cheap cars in Peru. The model that concentrates the highest percentage of sales is the Miso, aimed at socioeconomic levels C and D. Due to the saturation of the main Miso market and new laws that regulate the importation of used cars, an unsatisfied market has been created, So Paico has increased its product portfolio by launching new models aimed at a higher socioeconomic class. The company is currently in a quandary as the board is considering importing a new low-cost truck model that would reinforce the image that Paico sells cheap and low-quality cars, negatively impacting the recent product line.